Forensic Performance Analysis of Load‐Limiting Devices in Automotive Seat Belt Retractors. Issue 3 (14th November 2018) - D'Aulerio, Louis; Whitman, Gary; Sicher, Larry; Cantor, Alan; Markushewski, Mike
Abstract: The introduction of frontal airbags and seatbelt pretensioners for front seat occupants provided an opportunity to address injuries caused by seatbelt loading by introducing load‐limiters, which were intended to reduce belt loading while maintaining proper restraint. Investigation and forensic analysis of real‐world crashes identified that the implementation of these devices, in some circumstances, increased the potential of injury. This paper focuses on the trade‐offs of load‐limiters, that is, the reduction loading to the occupant versus the corresponding increase in seatbelt webbing and occupant movement. If the additional webbing introduced is not controlled, the risk of injury to the occupant is increased and could result in more frequent and severe injuries rather than a reduction. This paper quantifies the webbing introduced by load‐limiter activation through forensic analysis of the seatbelt involved in real‐world crashes and testing and assesses its effect on the injuries sustained by the occupant.